Phylogenetic Analysis of Cytochrome Oxidase I from Buduk Toads Duttaphrynus melanostictus and Phrynoidis asper from Bogor - Muhammad Dailami; I Made Artika; Mirza Dikari Kusrini; Dodi Safari (Current Biochemistry, 2016)
Indonesia have high diversity of Amphibians. Amphibians have an important role in ecosystem and produce many bioactive peptides. However, the genetic information of amphibians from Indonesia is very limited, especially Duttaphrynus melanostictus and Phrynoidis asper. The aims of this study are to determine the nucleotide sequence of cytochrome oxidase I (COI) from D. melanostictus and P. asper, to analyze their genetic diversity and their phylogenetic relationship. A total 668 base pairs of COI gene fragment were successfully amplified and their nucleotide sequence determined. P. asper (5 haplotypes) samples group have high haplotype diversity compared to D. melanostictus (1 haplotype). The results of Basic Local Alignment Search Tools (BLAST) to the NCBI and BOLD database, showed 99 % - 100 % identity to sequence of D. melanostictus. For the sequence of P. asper showed 99.23 % identity to sequence P. asper in BOLD database. There was no sequence of COI gene of P. asper in NCBI database. Genetic relationship among species in family Bufonidae, indicated that D. melanostictus has closer relation to P. asper than to another species, inspite of their pharapyletic characteristic. For intern species relationship of D. melanostictus, the data showed that D. melanostictus from Bogor have closer relationship to D. melanostictus from India than D. melanostictus from China.